"Your research or my tinkering won't help": On (the lack of) Climate Adaptation Imaginaries in the Swedish Arctic - Söderlund Kanarp, Christoffer (ELSEVIER SCI LTD, 2024)
Developing 'Climate Adaptation Imaginaries', this paper explores visions of futures in relation to climate change and adaptation in the Swedish Arctic, a region where climatic changes are rapid and pronounced. The analysis draws on interviews with civil servants working with adaptation, fieldwork in the region of Norrbotten in Sweden, and relevant documents. The analysis focuses on future visions and whether, and how, they incorporate adaptation to the climate crisis as a strategy to achieve the vision. Particular focus is given to how adaptation is understood in terms of approach (reactive vs. proactive), aim (incremental vs. transformational) and focus (direct effects, or whether transboundary effects are included). Four different kinds of visions emerge in the material: economic growth coupled with a reactive approach; 'green' economic growth with proactive and incremental adaptation; a transformed locally anchored and regenerative society; and finally, a range of dystopia(s). It is only the two visions based on economic growth that are collectively held, materially embedded and hold political influence in the region. A variety of dystopias emerge as the main alternative presented by civil servants. This leaves adaptation guided by at best proactive, incremental and short-term focused strategies, and at worst driven by disparate dystopic visions.